River fisheries in Brazil: a review - Petrere, M. (Wiley, 1989)
Riverine fisheries in Brazil are reviewed. There is a broad description of the environment and the fish, and arguments for the high diversity of fish fauna diversity are examined. The country is divided into five large river basins and the fisheries are described in relation to the main fish species caught, the main gear employed, and the fishing strategies. Exotic species introduction is discussed along with strategies for fish stock management. Effects of dams on resident fish stocks and consequences for the small scale fisheries are discussed and compared with the effects of pollution. -Author
Keywords: dam; environment; fish species; fish stock management; fishery; pollution; river fishery; Brazil